2008
DOI: 10.1016/j.ast.2007.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Numerical prediction and wind tunnel experiment for a pitching unmanned combat air vehicle

Abstract: The low-speed flowfield for a generic unmanned combat air vehicle (UCAV) is investigated both experimentally and numerically. A wind tunnel experiment was conducted with the Boeing 1301 UCAV at a variety of angles of attack up to 70 degrees, both statically and with various frequencies of pitch oscillation (0.5, 1.0, and 2.0 Hz). In addition, pitching was performed about three longitudinal locations on the configuration (the nose, 35% MAC, and the tail). Solutions to the unsteady, laminar, compressible Navier-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…This is not always the case though. Experiments by Forestier et al [11] on a cavity with an L/D ratio of 0.42 found that the shear had an high growth rate for the first 25% of the length (dδ m /dx = 0.12), which then reduced to a lower value (dδ m /dx = 0.042). This was also observed numerically by Larchevêque et al [23] for the same cavity.…”
Section: Flow-field Visualisationsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is not always the case though. Experiments by Forestier et al [11] on a cavity with an L/D ratio of 0.42 found that the shear had an high growth rate for the first 25% of the length (dδ m /dx = 0.12), which then reduced to a lower value (dδ m /dx = 0.042). This was also observed numerically by Larchevêque et al [23] for the same cavity.…”
Section: Flow-field Visualisationsmentioning
confidence: 96%
“…Cummings et al [10] experimentally and numerically investigated a similar configuration designated 1301. Similar to the studies of the 1303 UCAV, agreement between the experimental and numerical data sets was only gained at angles of attack below 15 degrees.…”
Section: Previous Work On Ucavs and Cavity Flowsmentioning
confidence: 98%
“…Experimental and numerical research into a low-velocity flow field for an unmanned AC were undertaken [20]. Experiment during WTT was conducted statically with different angles of attack up to 70°.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Cummings et al 24 compute the flowfield over a Λ = 50 o UCAV configuration with rounded leading edges at a Re of the order of 10 5 . There is a correspondence between the computed upstream movement of the bursting point with α over the UCAV configuration and the upstream movement of the S 2 bending point observed over wing III.…”
Section: Lift Coefficient Drag Coefficientmentioning
confidence: 99%